Peningkatan Hasil Belajar Menggunakan Model Kooperatif Tipe Two Stay Two Stray Berbantuan Wordwall di Sekolah Dasar - Dewa Dela Sari; Hamimah Hamimah (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2023)
The background of this study is the problem of student learning outcomes that are still lacking in integrated thematic learning in class V of elementary school. This study aims to describe the implementation of the cooperative learning model with the two stay two stray types assisted by word wall media in grades V SDN 10 Bandar Buat Padang City. This type of research is classroom action research using qualitative and quantitative approaches. The research was carried out in two cycles referring to procedures: planning, implementing, observing, and reflecting. The subjects of the study were teachers and fifth-grade students at SDN 10 Bandar Buat City of Padang, totalling 24 students. The results showed an increase in learning outcomes. Cycle I obtained: a) an increase in planning observation scores from 92.71% to 95.83%; b) Teacher activity increased from 83.75% to 95%; c) student activity increased from 83.75% to 95%; d) while learning outcomes also increased from 75.61 to 91.32. Thus, the application of the Two Stay Two Stray cooperative model assisted by Wordwall media can improve student learning processes and outcomes.